Counseling on Post-Sports Injury Recovery in Gymnastic Athletes - Idah Tresnowati; Gilang Nuari Panggraita; Lukman Alfaris; Nurul Aqil Nahari (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Injury is one of the risks often experienced by floor gymnastics athletes due to the high intensity of training and the complexity of the movements that must be performed. Therefore, counseling on post- injury recovery plays an important role in ensuring an optimal healing process, preventing recurrent injuries, and improving athlete performance. This recovery process includes various aspects, starting from initial treatment with the RICE method (Rest, Ice, Compression, Elevation), a structured rehabilitation program, meeting the right nutritional needs, to implementing injury prevention strategies for the future. In addition to physical aspects, psychological factors also play a role in helping athletes overcome mental challenges during recovery. With this counseling, it is hoped that athletes, coaches, and medical personnel can understand the importance of effective injury management, so that they can support athletes in returning their physical and mental conditions to optimal levels.